Implementación de la transformada wavelet sobre un sistema embebido para el pre-procesamiento de señales unidimensionales no estacionarias - Ruiz Salazar, Jeferson (Ingenierias, 2017)
Several methods are used for signal processing, one of them is the Wavelet Transform (WT) algorithm. The WT is employed in the field of signal denoising; it has proved to be a tool that fits effectiveness in terms of execution time and precision. In this project, WT implementation on FPGA is proposed for denoising one-dimensional non-stationary signals. WT has been represented by the lifting method using four decomposition levels. To verify the design four EEG signals sampled at 100Hz collected from BCI competition III, corrupted by white Gaussian noise 20dB of SNR were used. The results were analyzed by two numerical evaluation criteria, such as Peak signal-to-noise ratio (PSNR) and mean square error (RMSE), which showed an improvement of 1.9 regarding RMSE and 1.7 concerning PSNR about the noisy signal.